2015
DOI: 10.1007/s13204-014-0390-6
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of heavy metals by magnetic nanoadsorbent: an equilibrium and thermodynamic study

Abstract: An efficient and new magnetic nanoadsorbent photocatalyst was fabricated by co-precipitation technique. This research focuses on understanding metal removal process and developing a cost-effective technology for treatment of heavy metal-contaminated industrial wastewater. In this investigation, magnetic nanoadsorbent has been employed for the removal of Zn(II) ions from aqueous solutions by a batch adsorption technique. The adsorption equilibrium data fitted very well to Langmuir and Freundlich adsorption isot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 22 publications
(20 reference statements)
4
16
0
Order By: Relevance
“…The objective of this study was the utilization of magnetite nanomaterials as adsorbent for the removal from wastewater of a resilient cationic surfactant, benzyldodecyldimethylammonium bromide (benzalkonium bromide). Taking into consideration the disadvantages of conventional methods and conventional adsorbent materials used for the wastewater treatment such as low efficiency for pollutants removal at low concentration, it was chosen a nanomaterial which have more advantages compared with the conventional ones: small particle size, increased surface area, therefore improving adsorption capacities for the removal of pollutants form wastewater [30,31]. Treatment of wastewater containing surfactants by adsorbent nanomaterials offered a non-polluting alternative to the standard one.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this study was the utilization of magnetite nanomaterials as adsorbent for the removal from wastewater of a resilient cationic surfactant, benzyldodecyldimethylammonium bromide (benzalkonium bromide). Taking into consideration the disadvantages of conventional methods and conventional adsorbent materials used for the wastewater treatment such as low efficiency for pollutants removal at low concentration, it was chosen a nanomaterial which have more advantages compared with the conventional ones: small particle size, increased surface area, therefore improving adsorption capacities for the removal of pollutants form wastewater [30,31]. Treatment of wastewater containing surfactants by adsorbent nanomaterials offered a non-polluting alternative to the standard one.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular kinetic models are Lagergren pseudo first-order and pseudo second-order kinetics. Among them, the pseudo second-order kinetic model has been regarded as the best fitted model with aqueous chromium adsorption onto different magnetic nanosorbents [11], aqueous Zn(II) ion adsorption onto Fe 3 O 4 NPs [9], and aqueous Cu(II) ion adsorption onto CMNPs [10].…”
Section: Adsorption Kinetics Modelmentioning
confidence: 99%
“…For the purpose of the present study, we refer to data formerly obtained in three other works. The extraction of zinc(II) ions via the bath adsorption process on magnetic Fe 3 O 4 nanoparticles (case study 1) from wastewater has already been carried out and reported on by Shirsath and Shirivastava [9], who concluded that the process could be influenced by different factors, such as the pH level, contact time (t), adsorbent dose, and initial concentration of Zn(II) ions. See Table 5 for a summary of the details.…”
Section: Data Collectionmentioning
confidence: 99%
“…These methods have been found to be limited, because of the high capital and operating costs or the infectiveness in meeting stringent effluent standards. Therefore several approaches have been studied for the development of inexpensive and abundant adsorbents such as sawdust [10], live biomass [11], clay [12,13] and agricultural byproducts, Zn(II) removal by magnetic nanoadsorbents [14][15][16][17]. Each methods has been found to be limited for the cost, complexity and efficiency, as well as secondary wastes, for example the electrolysis process often take higher operational costs and chemical precipitation may generates secondary wastes [18].…”
Section: Introductionmentioning
confidence: 99%